Post-translational modification of PII signal transduction proteins - Merrick, Mike (Frontiers in Microbiology, 2015)
The PII proteins constitute one of the most widely distributed families of signal transduction proteins in nature. They are pivotal players in the control of nitrogen metabolism in bacteria and archaea, and are also found in the plastids of plants. Quite remarkably PII proteins control the activities of a diverse range of enzymes, transcription factors and membrane transport proteins, and in all known cases they achieve their regulatory effect by direct interaction with their target. PII proteins in the Proteobacteria and the Actinobacteria are subject to post-translational modification by uridylylation or adenylylation respectively, whilst in some Cyanobacteria they can be modified by phosphorylation. In all these cases the protein’s modification state is influenced by the cellular nitrogen status and is thought to regulate its activity. However, in many organisms there is no evidence for modification of PII proteins and indeed the ability of these proteins to respond to the cellular nitrogen status is fundamentally independent of post-translational modification. In this review we explore the role of post-translational modification in PII proteins in the light of recent studies.